1, 25-Dihydroxyvitamin D3 and extracellular calcium promote mineral deposition via NPP1 activity in a mature osteoblast cell line MLO-A5. (5th September 2015) - Yang, Dongqing; Turner, Andrew G.; Wijenayaka, Asiri R.; Anderson, Paul H.; Morris, Howard A.; Atkins, Gerald J.
Highlights: 1, 25D and calcium effects on MLO-A5 osteoblast mineralisation were tested. 1, 25D induced calcium-dependent matrix mineralisation. 1, 25D and extracellular calcium induced Enpp1 gene expression evidenced at both mRNA and protein levels. Addition of Enpp1 siRNA and NPP1 inhibitor, PPADS, abrogated the effect of 1, 25D/Ca 2+ on mineralisation. Abstract: While vitamin D supplementation is common, the anabolic mechanisms that improve bone status are poorly understood. Under standard mineralising conditions including media ionised calcium of 1.1 mM, 1, 25-dihydroxyvitamin D3 (1, 25D) enhanced differentiation and mineral deposition by the mature osteoblast/pre-osteocyte cell line, MLO-A5. This effect was markedly increased with a higher ionised calcium level (1.5 mM). Gene expression analyses revealed that 1, 25D-induced mineral deposition was associated with induction of Enpp1 mRNA, coding for nucleotide pyrophosphatase phosphodiesterase 1 (NPP1) and NPP1 protein levels. Since MLO-A5 cells express abundant alkaline phosphatase that was not further modified by 1, 25D treatment or exposure to increased calcium, this finding suggested that the NPP1 production of pyrophosphate (PPi) may provide alkaline phosphatase with substrate for the generation of inorganic phosphate (Pi). Consistent with this, co-treatment with Enpp1 siRNA or a NPP1 inhibitor, PPADS, abrogated 1, 25D-induced mineral deposition. These data demonstrate that 1, 25D stimulates osteoblast differentiation and mineral deposition, and interacts with the extracellular calcium concentration. 1, 25D regulates Enpp1 expression, which presumably, in the context of adequate tissue non-specific alkaline phosphatase activity, provides Pi to stimulate mineralisation. Our findings suggest a mechanism by which vitamin D with adequate dietary calcium can improve bone mineral status.